Challenging primary school students’ attitude toward calculators - Russasmita Sri Padmi (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Calculators are a viable option for educational technology in developing countries due to its affordability and accessibility; it is also supported by literature to have positive effects on the students’ acquisition of mathematics concepts and skills positively. However, the stakeholders of education in Indonesia often stigmatize the use of calculators in mathematics classrooms, especially in primary school. This is in contrast with the policy of many developing countries which include calculator as one of the educational technologies to be used in the classroom. This study aims to investigate the effect of calculator-enhanced mathematics lessons on the attitude of primary school students’. Fourth-grade students (n = 95) in four separate schools with minimum calculator experience participated in this study. The questionnaire was administered before and after the lesson to record their attitude. The use of a well-established scale ensured validity, while the Cronbach-Alpha score confirmed reliability. Data analysis was conducted through the comparison of mean value between pre- and post-questionnaires scores. The finding suggests that while the effect on attitude toward mathematics is somewhat mixed, there is a significant improvement in the students’ attitude toward using calculators to learn mathematics. Calculator-enhanced mathematics lessons help the students foster more positive attitudes toward calculators. The finding of the present study is expected to help teachers to challenge the stigma about calculator and thus can benefit from calculator to enhance their lesson.